A Call for a Stroke Referral Network Between Primary Care and Stroke-Ready Hospitals in the Philippines: A Narrative Review. Issue 6 (November 2021) - Espiritu, Adrian I.; San Jose, Maria Cristina Z.
Abstract : Background: The increasing stroke burden, inequity in the distribution of local neurologists, and the recent signing of the Universal Health Care Law in the Philippines provide compelling reasons for policy-makers to devise strategies to establish networks between primary care and stroke-ready hospitals. In this review, we explored the current literature and evidence that emphasized the roles of primary care providers (PCPs) and specialists, care transition, and telemedicine/teleneurology in various stages of stroke management. Review Summary: Clear delegation of stroke care responsibilities among PCPs and specialists is needed. Due to the limited number of specialists/neurologists, PCPs may contribute to addressing the insufficiency of community knowledge of acute stroke symptoms/risk factors, coordination with specialists and stroke-ready hospitals during acute stroke, and continuity of care during the poststroke stage. At present, the Philippines has only 49 stroke-ready hospitals; thus, an efficient and functional referral system for the care transition between the PCPs and specialists must be organized in our country. To provide remote access to expert stroke care for underserved areas and to increase thrombolysis utilization, the establishment of an effective telestroke system is indispensable. The empowerment of PCPs in teleneurology may assist in strengthening communication and networking with specialists with the ultimate goal of improving patient outcomes. Conclusions: In the era of Universal Health Care in the Philippines, the roles of PCP and specialists must be delineated. Increased access to stroke care through the establishment of networks among PCPs and stroke-ready hospitals (ie, via effective transition of care/teleneurology) must be prioritized especially in resource-constrained settings.